Magnesium in drinking water supplies and mortality from acute myocardial infarction in north west England. Issue 4 (1st October 1999) - Maheswaran, R; Morris, S; Falconer, S; Grossinho, A; Perry, I; Wakefield, J; Elliott, P
Abstract : OBJECTIVES: To examine whether higher concentrations of magnesium in drinking water supplies are associated with lower mortality from acute myocardial infarction at a small area geographical level; to examine if the association is modified by age, sex, and socioeconomic deprivation. DESIGN: Small area geographical study using 13 794 census enumeration districts. Water constituent concentrations (magnesium, calcium, fluoride, lead) measured at water supply zone and assigned to enumeration districts. SETTING: 305 water supply zones in north west England. SUBJECTS: Resident population of 1 124 623 men and 1 372 036 women (1991 census) aged 45 years or more. MAIN OUTCOME MEASURE: Mortality from acute myocardial infarction, International Classification of Diseases, ninth revision (ICD-9) 410. Subsidiary analysis examined deaths from ischaemic heart disease, ICD 410–414. RESULTS: There were 21 339 male and 17 883 female deaths from acute myocardial infarction in 1990–92. Drinking water magnesium concentrations in water zones ranged from 2 mg/l to 111 mg/l (mean (SD) 19 (20) mg/l, median 12 mg/l); 24% of variation in magnesium concentrations was within zone and 76% was between zone. The relative risk of mortality from acute myocardial infarction (standardised for age, sex, and Carstairs deprivation quintile) for a quadrupling of magnesium concentrations in drinking water (for example, 20 mg/l v 5 mg/l) was 1.01 (95% confidence interval (CI) 0.99 to 1.03). When adjusted for north-south and east-west trends in mortality from acute myocardial infarction and for drinking water calcium, fluoride, and lead concentrations, this relative risk was 1.01 (95% CI 0.96 to 1.06). There was no evidence of a protective effect for acute myocardial infarction even among age, sex, and deprivation groups that were likely to be relatively magnesium deficient. For ischaemic heart disease mortality there was an apparent protective effect of magnesium and calcium (with calcium predominating in the joint model), but these were no longer significant when the geographical trends were incorporated. CONCLUSIONS: No evidence was found of an association between magnesium concentrations in drinking water supplies and mortality from acute myocardial infarction. These results do not support the hypothesis that magnesium is the key water factor in relation to mortality from heart disease.